The Study of the Number of Most Medicine Use in the Two Biggest Diseases in Antara Public Health Centers Makassar City - Hasyim, Muhammad Farid; Alfafa, Muhammad Fadli (Politeknik Sandi Karsa, 2021)
The medicine plays an important role in health services. In drug use the most important thing step should be done is correct diagnosis so can give a rational prescription, effective, secure and economical. This research used descriptive method with the aim to know the highest number of drug use in the 2 largest diseases namely ISPA and GASTRITIS. The collecting data was done by using the prescription on the patients of ISPA and GASTRIS that have been hospitalized at Antara public health center on January to March 2021. The result of this research can be inferred that on January to March, the drug use rather decrease, it’s caused by the influence by a good weather.in January to March. The number of patients infected with ISPA as many as 204 and the largest drug use with dexamethasone as much as 1.770, meanwhile the patients infected with Gastris as many as 180 and the largest drug use with ranitidine as much as 1460